Supramolecular metallogel that imparts self-healing properties to other gel networks - Feldner, Tobias; Haering, Marleen; Saha, Subhadeep; Esquena, Jordi; Banerjee, Rahul; Diaz, David Diaz (Chemistry of Materials, 2016)
A unique proton conductive and moldable supramolecular metallogel (CuA-Ox-gel) made upon mixing at room temperature well-defined stock solutions of Cu(OAc)(2). H2O and oxalic acid dehydrate was found to have self-healing properties. Remarkably, the system also displayed an unprecedented ability to impart self-healing properties to other gel networks lacking this capacity. A self-healed CuA-Ox metallogel was found to have essentially the same nanofibrillar morphology, thermal stability, rheological properties, and conductivity as the freshly prepared sample. The discovery also allowed the fabrication of self-healing conductive composites containing conductive carbonaceous materials. Overall, this work serves as a proof of concept for the transfer of self-healing properties between completely different gel networks.